An Analysis of Sibling Correlations in Health using Latent Variable Models. (20th February 2017) - Halliday, Timothy J.; Mazumder, Bhashkar
Abstract: We investigate sibling correlations in youth health status using the Panel Study of Income Dynamics. We do so by estimating the covariance structure of a system of equations in latent variables using methods that have hitherto not been used in the literature on intergenerational transmissions of health. Across a battery of outcomes, we find that between 50 and 60% of health status can be attributed to shared familial or neighborhood characteristics. Taking the principal component across all outcomes, we obtain a sibling correlation of about 53%. These estimates, which are larger than previous estimates of sibling correlations in health that rely on linear models, are more in‐line with sibling correlations in income and suggest that health status, like other measures of socioeconomic success, is strongly influenced by family background. Copyright © 2017 John Wiley & Sons, Ltd.